Rice farming in Myanmar: Effects of adoption of best management practices on livelihoods and food security of rural women - Connor, Melanie (International Rice Research Institute, 2018)
Presented by Melanie Connor (IRRI), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.